Watching Dallas / Soap Opera and the Melodramatic Imagination - Ang Ien (Rouledge, 1985)
This book introduces the reader to insights from recent film and television studies, and draws on theories of culture and ideology in a concrete and accessible way. Preface, Introduction, Dallas Between Reality and Fiction, Dallas and the Melodramatic imagination, Dalla and the Ideology of Mass Culture, Dallas and Feminism, Notes, Index.